Extracellular matrix biomarker, fibulin-1, is closely related to NT-proBNP and soluble urokinase plasminogen activator receptor in patients with aortic valve stenosis (the SEAS study). - Ruan Kruger (Public Library of Science (PLoS), 2014)
Background Fibulin-1, a circulating extracellular matrix glycoprotein, has been associated with arterial disease and elevated N-terminal prohormone B-type natriuretic peptide (NT-proBNP) in diabetes. Soluble urokinase plasminogen activator receptor (suPAR), a marker of inflammation, has been associated with subclinical atherosclerosis. Therefore, we aimed to explore the interplay between these biomarkers and mild to moderate aortic valve stenosis (AS). Methods In 374 patients with mild to moderate AS, we investigated the relationship of fibulin-1 with NT-proBNP, levels of suPAR and the degree of AS at baseline and after one and four years of treatment with Simvastatin 40 mg and Ezetimibe 10 mg or placebo. Results During treatment, fibulin-1 became more closely associated with NT-proBNP (βyear0 = 0.10, p = 0.08, βyear1 = 0.16, p = 0.005, βyear4 = 0.22, p<0.001) and suPAR (βyear0 = 0.05, p = 0.34, βyear1 = 0.16, p = 0.006, βyear4 = 0.13, p = 0.03) at the expense of the association to aortic valve area index (AVAI) (βyear0 = -0.14, p = 0.005, βyear1 = -0.08, p = 0.11, βyear4 = -0.06, p = 0.22) independently of age, gender, creatinine, and serum aspartate aminotransferase (Adj.Ryear02 = 0.19, Adj.Ryear12 = 0.22, Adj.Ryear42 = 0.27). Fibulin-1 was unrelated to aortic regurgitation, left ventricular mass, and ejection fraction. In patients with baseline AVAI<0.58 cm2/m2 (median value), fibulin-1 was more closely associated to NT-proBNP (βyear0 = 0.25, βyear1 = 0.21, βyear4 = 0.22, all p<0.01), and suPAR (βyear0 = 0.09, p = 0.26, βyear1 = 0.23, βyear4 = 0.21, both p<0.01) independently of age, gender, AST and treatment allocation. Conclusions Increased levels of fibulin-1 were independently associated with higher levels of suPAR and NT-proBNP especially in patients with lower AVAI, suggesting that fibulin-1 may be an early marker of AS as well as cardiac fibrosis secondarily to elevated left ventricular hemodynamic load.